2021
DOI: 10.1139/facets-2020-0104
|View full text |Cite
|
Sign up to set email alerts
|

Inoculating rhizome-propagated Sporobolus pumilus with a native mycorrhizal fungus increases salt marsh plant growth and survival

Abstract: Salt marshes are ecosystems of significant ecological importance for coastal stability and fundamental roles in marine ecosystems. Salt marshes are declining due to anthropogenic and natural causes including sea level rise. Coastal restoration efforts have increased worldwide, but many fail in long-term coastal stability. We used a naturally occurring arbuscular mycorrhizal fungus (AMF) to test whether survival and early growth of the salt marsh grass Sporobolus pumilus (formerly Spartina patens) improved unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(21 reference statements)
0
0
0
Order By: Relevance
“…The Driver Hypothesis proposes that AM fungi are a key driver in maintaining and explaining plant diversity by selective association with plants and by doing so they shape the aboveground plant communities (Hart et al, 2001). Some support comes from studies showing plants with stronger associations with AM fungi have higher survival rates and are more competitive in nutrient-poor soils (Johnson et al, 2003;d'Entremont et al, 2021a), while others have shown that AM fungi can increase plant diversity by increasing the total number of species that can coexist in a given area (Van Der Heijden and Scheublin, 2007). In contrast, the Passenger Hypothesis proposes that although AM fungi are important for plant growth and survival, they do not play a significant role in regulating plant diversity or community composition and that plant community composition has control over this interaction (Grman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The Driver Hypothesis proposes that AM fungi are a key driver in maintaining and explaining plant diversity by selective association with plants and by doing so they shape the aboveground plant communities (Hart et al, 2001). Some support comes from studies showing plants with stronger associations with AM fungi have higher survival rates and are more competitive in nutrient-poor soils (Johnson et al, 2003;d'Entremont et al, 2021a), while others have shown that AM fungi can increase plant diversity by increasing the total number of species that can coexist in a given area (Van Der Heijden and Scheublin, 2007). In contrast, the Passenger Hypothesis proposes that although AM fungi are important for plant growth and survival, they do not play a significant role in regulating plant diversity or community composition and that plant community composition has control over this interaction (Grman, 2012).…”
Section: Introductionmentioning
confidence: 99%